2021
DOI: 10.3390/ijms22073304
|View full text |Cite
|
Sign up to set email alerts
|

The PI3Kδ Inhibitor Idelalisib Diminishes Platelet Function and Shows Antithrombotic Potential

Abstract: Background: Clinical management of ischemic events and prevention of vascular disease is based on antiplatelet drugs. Given the relevance of phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) as a candidate target in thrombosis, the main goal of the present study was to identify novel antiplatelet agents within the existing inhibitors blocking PI3K isoforms. Methods: We performed a biological evaluation of the pharmacological activity of PI3K inhibitors in platelets. The effect of the inhibitors was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…More concrete evidence of novel targets to be exploited therapeutically for vascular disorders are provided by two additional works that focus on two major pathogenetic mechanisms of vessel disease, namely thrombosis and arterial restenosis [ 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More concrete evidence of novel targets to be exploited therapeutically for vascular disorders are provided by two additional works that focus on two major pathogenetic mechanisms of vessel disease, namely thrombosis and arterial restenosis [ 5 ].…”
mentioning
confidence: 99%
“…Available drugs able to interfere with platelet aggregation are associated with increased risk of hemorrhage, warranting the development of effective, yet safer, anti-platelet drugs. The work by Barrachina et al has identified a compound, called Idelalisib, which potently inhibits platelet adhesion and aggregation by blocking Phosphoinositide 3-kinases (PI3K), but shows minimal bleeding effects in mice, compared to standard anti-platelet therapy, such as aspirin and clopidogrel, in mouse models [ 5 , 6 ].…”
mentioning
confidence: 99%